The Effectiveness of Acupressure in Reducing Pain After Coronary Angiography: a Systematic Review - Elvi Kurnia Damayanti; Asroful Hulam Zamroni; Johanes Eban B. Dorman; Rizki Nur Azhadin; Ninuk Dian Kurniawati (Jurnal Ners, 2025)
Coronary angiography, a critical diagnostic tool for coronary artery disease, often results in post-procedural pain that affects patient recovery and satisfaction. Acupressure, a non-invasive technique rooted in traditional Chinese medicine, has shown promise in reducing pain by stimulating endorphin release and enhancing physiological responses. This systematic review aimed to evaluate the effectiveness of acupressure in managing pain among patients undergoing coronary angiography. Four databases (Scopus, PubMed, ProQuest, and ScienceDirect) were searched for relevant articles published between 2020 and 2025, using keywords such as "acupressure," "pain," and "coronary angiography." Joanna Briggs Institute guidelines were used to assess study quality. Seven randomized controlled trials involving 774 participants were included. All studies reported significant pain reduction after acupressure interventions (p < 0.05), with durations ranging from 15 to 120 minutes at points like LI4 and PC6. Acupressure not only reduced pain but also stabilized vital signs and reduced anxiety. These findings suggest that acupressure is an effective intervention for post-coronary angiography pain, providing a strong basis for its integration into clinical practice. Further research is needed to standardize protocols and explore long-term effects.